Faktor-Faktor Yang Mempengaruhi Permintaan Ekspor Kopi Indonesia Ke Amerika Serikat Tahun 1985-2018 - Yustinus Wahyudi; Anna Wijayanti; Sotya Fevriera (Journal of Economics Development Issues, 2021)
Coffee has a pretty good prospect in Indonesia with quite large production. However, Indonesian coffee trade still faces many obstacles. One of them, coffee is less competitive with coffee from other countries in United States which is Indonesia's main export destination. The purpose of this study is to determine the factors affecting the volume of coffee exports to United States in 1985-2018. This study uses secondary time series data collected from the Central Bureau of Statistics, the World Bank and the Ministry of Agriculture as well as a multiple regression model with the least squares method. The results show that the real GDP per capita of the United States, the real effective exchange rate of the United States, Indonesian inflation, world coffee prices, world tea prices and United States populations have an effect on Indonesian coffee exports demand. Individually, inflation in Indonesia, world tea prices and United States populations have significant positive effect while the real effective exchange rate of the United States have significant negative effect on Indonesian coffee exports demand from United States, but the real GDP per capita of the United States and world coffee prices have no effect on Indonesian coffee exports demand from United States.